A computational study of adsorption and activation of CO2 and H2 over Fe(1 0 0) surface. (September 2016) - Wang, Haozhi; Nie, Xiaowa; Guo, Xinwen; Song, Chunshan
Graphical abstract: Highlights: Adsorption configurations of CO2 and H2 on Fe(1 0 0) were systematically examined. The minimum energy pathways for H2 dissociation were identified. CO2 adsorption stability is significantly impacted when H* coverage becomes high. Abstract: Periodic density functional theory calculations were performed to investigate the adsorption and activation of CO2 and H2 over Fe(1 0 0) surface. Four stable adsorption configurations of CO2 were identified and the energetically most stable adsorption was found to occur on the 4-fold hollow site where the C atom of CO2 sits right above the second layer Fe atom and the two O atoms bound at the center of two FeFe bridge bonds on the surface. H2 molecule dissociates to H* atoms upon adsorption. Only when H2 adsorbs on the top sites of the metal surface it can be stabilized in an associative or molecular form. Small energy barriers were found for H2 dissociation on Fe(1 0 0) which indicates that H2 dissociates very fast on the catalyst surface. CO2 adsorption stability could be influenced by the surface coverage of H*. We observed a significant decrease of CO2 adsorption strength when surface H* coverage becomes higher than 2/3 ML.